Pengaruh Penggunaan Alat Peraga Sederhana terhadap Keaktifan Siswa dalam Pembelajaran IPA siswa SMP - Emy Ramadhani; Wili Andrian; Anggara Wira Mada; Lestiani; Indri Herlina; Siti Nur Linda Hariyani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the influence of simple teaching aids on student activeness in science learning at the junior high school level. The background of the research arises from the low level of student participation in science classes, which are still dominated by lecture-based instruction. A descriptive qualitative approach was employed involving seventh- and eighth-grade students at SMPN 15 Bengkulu City. Data were collected through classroom observations, teacher interviews, and documentation, then analyzed using the Miles & Huberman model. The findings indicate that the use of simple teaching aids such as real plants, organ illustrations, microscopes, and mannequins successfully enhances various forms of student activeness, including observing, questioning, discussing, using tools, and drawing conclusions from observations. Levels of activeness varied between classes depending on the type of teaching aid and the complexity of the material; seventh-grade students tended to show higher verbal and observational engagement, while eighth graders demonstrated more motoric and cognitive involvement. The use of simple teaching aids was proven to make science learning more concrete, interactive, and aligned with the principles of the Merdeka Curriculum. The study concludes that simple teaching aids play an important role in improving student activeness and the overall quality of science learning. These findings may serve as recommendations for science teachers in designing more meaningful and student-centered instruction.